Acute heart failure - Abadie, Eric 1964- (Springer, 2008)
For many years, there has been a great deal of work done on chronic congestive heart failure while acute heart failure has been considered a difficult to handle and hopeless syndrome. However, in recent years acute heart failure has become a growing area of study. There has been considerable amounts of new data reported and many new concepts have been proposed in the last 3-4 years looking at the epidemiology, diagnostic and treatment of acute heart failure.